La responsabilidad de los abogados por la justicia de sus casos - Kennedy, Duncan (2008)
"Originally published as 'The responsibility of lawyers for the justice of their causes' in Texas Tech. Law Review, no. 18, 1987. The editors thank the author for permission to translate and publish it in this journal. Spanish translation by Luciana Ekmekdjian, Professor of Constitutional Law, Faculty of Law, University of Buenos Aires, reviewed by the author and Mary Beloff."